(untitled) (Південний архів (історичні науки), 2025)
The main purpose of the article is to analyze the transformation of the school subject “Civic Education” that fosters students’ democratic identity in the context of the full-scale war in Ukraine. The study aims to define new content priorities that should be integrated into the updated curriculum in response to martial law, psychological challenges, and information threats.The research methodology is based on critical analysis of current curricula, regulatory frameworks, expert assessments, and comparative examination of European models of civic education, particularly the Reference Framework of Competences for Democratic Culture.The results substantiate the need to include in the school course several new topics: international humanitarian law, protection of internally displaced persons, the role of human rights institutions, foundations of psychological self-regulation, media literacy and digital security, as well as youth participation in volunteer and civic initiatives. The article highlights the importance of shaping students’ awareness of Ukraine’s European development trajectory. The conclusion emphasizes that the content update should be grounded in the principles of resilience, legal awareness, civic engagement, and critical thinking. Reform efforts should also involve modern pedagogical methods–project-based learning, interdisciplinary integration, cooperation with civil society organizations, and the use of real-life case studies. Such modernization will ensure the development of civic competences essential for adapting to wartime conditions, post-war recovery, and democratic nation- building.